La emergencia de la delincuencia organizada en un análisis genealógico de la tradición Nietzsche-Foucault - Arriaga Ornelas , José Luis (Nómadas. Critical Journal of Social and Juridical Sciences, 2008)
In this work the main elements of the behavior recover genealogical to apply them to the analysis of an object of the contemporary thought: the organized delinquency. The intention is to prove the utility of that behavior to give account of the form in which a series of rules of formation of objects takes body in techniques from exercise of the control in the present society.